Luke’s use of a Departure-Arrival Formula in the Book of Acts - Wilson, Mark W. (Scriptura, 2022)
When Saul began to persecute the believers in Jerusalem after Stephen’s martyrdom, everyone except the apostles was scattered throughout Judea and Samaria. Among those who began to preach the word was Philip, who went to Samaria proclaiming Christ. Significant to the opening verses of this pericope is Luke’s first use of a departure-arrival formula in Acts. This formula, featuring verbal doublets with stock elements, also introduces several other journeys that involve other characters in later chapters. This article will discuss the characteristics of this formula and the texts in Acts where it is used. It will suggest literary precedents for the formula in the Septuagint. Finally, it will discuss other pericopae in Acts where travel is divinely directed and why the formula is not used in them.